Smart supramolecular sensing with cucurbit[n]urils: probing hydrogen bonding with SERS. (21st September 2017) - de Nijs, Bart; Kamp, Marlous; Szabó, Istvan; Barrow, Steven J.; Benz, Felix; Wu, Guanglu; Carnegie, Cloudy; Chikkaraddy, Rohit; Wang, Wenting; Deacon, William M.; Rosta, Edina; Baumberg, Jeremy J.; et al.
Abstract : Rigid gap nano-aggregates of Au nanoparticles formed using cucurbit[ n ]uril (CB[ n ]) molecules are used to investigate the competitive binding of ethanol and methanol in an aqueous environment. We show it is possible to detect as little as 0.1% methanol in water and a ten times higher affinity to methanol over ethanol, making this a useful technology for quality control in alcohol production. We demonstrate strong interaction effects in the SERS peaks, which we demonstrate are likely from the hydrogen bonding of water complexes in the vicinity of the CB[ n ]s.